Study of Tantalum Substituted Potassium Tungsten Bronzes - Shakil, Md Mahbubur R; Debnath, Tapas; Ruscher, Claus H; Hussain, Altaf (Journal of the Bangladesh Chemical Society, 2012)
A series of compounds KxTayW1-yO3 with x = 0.30, 0.00 ? y ? 0.30 and x = 0.55, 0.00 ? y ? 0.10 were synthesized by conventional solid-state method. The samples were characterized using XRD and FTIR spectroscopy. X-ray powder patterns reveal that the samples with compositions x = 0.30, y ? 0.30 show hexagonal tungsten bronze (HTB) type phase and the samples with x = 0.55, 0.02 ? y ? 0.10 show a mixture of two phases (K-HTB and tetragonal potassium tungsten bronze, K-TTB). The samples of the system, K0.30TayW1-yO3 with 0.00 ? y ? 0.15 shows no significant change in the cell parameters. However, for the composition y > 0.15, the cell parameter a decreases and c increases with increasing Ta content, which may be explained by the ordering of Ta for y > 0.15 suggesting the transformation to another space group. The appearance of absorption peak in the infrared absorption spectra of K0.3TayW1-yO3, y > 0.10 samples indicate the transition to non-metallic phase. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11770 Journal of Bangladesh Chemical Society, Vol. 25(1), 38-45, 2012